2018
DOI: 10.1021/acs.jpcc.8b05482
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, Dissociation, and Spillover of Hydrogen over Au/TiO2 Catalysts: The Effects of Cluster Size and Metal–Support Interaction from DFT

Abstract: The effects of cluster size and metal–support interaction on the catalytic activity of Au nanoparticles supported on anatase TiO2(101) and (001) surfaces for H2 adsorption, activation and dissociation were investigated by periodic density functional theory (DFT) calculations. On the stoichiometric TiO2 surfaces, it was found that the adsorptions of both Au clusters and H2 molecules are sensitive to the cluster size of gold, and the (001) facet with “soft” lattice and coordination unsaturated atoms on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 146 publications
1
31
0
Order By: Relevance
“…The results, presented on Table S13, clearly show that the conversion improvement linked to the Ni on Ni/TiO2-anatase is much higher than the one linked to the TiO2anatase support itself. The precise role of the H species is still unclear, but it is worth mentioning that TiO2 reduction by hydrogen spillover has been reported [94][95][96]. Additionally, it was reported that on Rh catalyst supported on CeO2 (another reducible support), the fraction of CO that undergoes dissociation increases significantly as the CeO2 surface is reduced [97].…”
Section: H2-tpd Experiments and Catalytic Tests To Assess Hydrogen Spillovermentioning
confidence: 99%
“…The results, presented on Table S13, clearly show that the conversion improvement linked to the Ni on Ni/TiO2-anatase is much higher than the one linked to the TiO2anatase support itself. The precise role of the H species is still unclear, but it is worth mentioning that TiO2 reduction by hydrogen spillover has been reported [94][95][96]. Additionally, it was reported that on Rh catalyst supported on CeO2 (another reducible support), the fraction of CO that undergoes dissociation increases significantly as the CeO2 surface is reduced [97].…”
Section: H2-tpd Experiments and Catalytic Tests To Assess Hydrogen Spillovermentioning
confidence: 99%
“…We choose such small size in order to keep the simulation cell as small as possible. Besides, many experimental studies have shown that such small clusters with various sizes can be easily deposited on the TiO 2 surface, being highly active catalysts for a broad class of reactions [25][26][27]. For supported Au 4 , we use a 1×4 anatase unit cell.…”
Section: Computational Setupmentioning
confidence: 99%
“…The hydrogen transfer can be well coupled with the spillover of active hydrogen at the metal-oxide interface with the -Ti-OH surface intermediate. 40 Therefore, we propose a plausible mechanism for active hydrogen transfer on the five-layer catalyst as shown in Figure 5 . The active hydrogen atoms from the decomposition of N 2 H 4 ·H 2 O (H-Ni) transfer from the Ni layer to the TiO 2 interlayer and further to the Pt interlayer for hydrogenation.…”
Section: Discussionmentioning
confidence: 92%